Pyrolysis and Morphology Behavior of EDTA-Na2Mg•4H2O and Coal Tar Pitch and Its Application for Porous Carbon - Zhang, Wen-Juan; Song, Shi-Hua; Tian, Wen-Hong (Journal of Spectroscopy, 2021)
Coal tar pitch (CTP) is a quite promising candidate for the production of porous carbons. Traditionally, the porous carbons are prepared by the heat treatment of carbon precursors in the presence of template and activator. In this paper, EDTA-Na2Mg•4H2O and CTP were mixed to produce porous carbons in the absence of template and activator, which were generated in situ by the heat treatment of EDTA-Na2Mg•4H2O. The pyrolysis and morphology behavior of the mixture of EDTA-Na2Mg•4H2O and coal tar pitch (EDTA-Na2Mg•4H2O@CTP) were studied by thermogravimetry and differential scanning calorimetry, Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. The characteristics of the obtained porous carbons were characterized by N2 adsorption-desorption isotherm. The results show that EDTA-Na2Mg•4H2O has a great influence on the pyrolysis and morphology of CTP. The pyrolysis behavior of CTP becomes complicated after the addition of EDTA-Na2Mg•4H2O for the physical and chemical changes of EDTA-Na2Mg•4H2O during the heat treatment. EDTA-Na2Mg•4H2O@CTP dehydrates at 160°C and decomposes Na2CO3 and MgO at 600°C. The surface morphology of EDTA-Na2Mg•4H2O@CTP changes with the EDTA-Na2Mg•4H2O content and heat treatment temperature. After acid washing of the product of EDTA-Na2Mg•4H2O@CTP heat-treated at 700°C, the obtained porous carbon material consists of micropores and mesopores. Its specific surface area is 574.18 m2 g−1 and the average pore width is 4.53 nm.